Dynamic Characteristics and HIV Infection of Men who have Sex with Men from 2011 to 2017 in Yinchuan, Ningxia, China - Wu, Zhong-Lan; Guan, Guang-Yu; Zhao, Jian-Hua; Ma, Xue-Min; Wang, Xue-Min; Yang, Dong-Zhi; Cao, Min; Rawle, Daniel J. (Current HIV Research, 2018)
Objectives: Ningxia Hui Autonomous Region, an important area for ethnic Hui settlement in Northwest China, is a low HIV prevalence region. However, HIV infection rates among men who have sex with men (MSM) in Ningxia have increased to an alarming level, despite scale-up of control measures in recent years. This study aimed to understand the demographical and sexual behavior dynamics of MSM and to explore the factors associated with HIV infection. Methods: Annual cross-sectional surveys were carried out among MSM during 2011 2017 in Yinchuan, the capital city of Ningxia. Information regarding social demographics, sexual behavior and HIV prevention knowledge was collected. Blood samples were taken for HIV, HCV serological and genetic analysis, and syphilis serological analysis. The dynamic trend was analyzed with trend χ2 test and factors associated with HIV infection were identified by multivariate logistic regression analysis. Results: The study found a decreasing trend for mean age of the MSM population over the study period. MSMs with a college education or higher increased significantly, while the proportions that were in a marriage significantly decreased over the study period. The rate of HIV positive among MSM increased during the study period (p<0.05), however, the rate of recently diagnosed infections decreased from 2012 (p<0.05). Overall, a very high proportion (98%) of MSM had basic knowledge of HIV prevention, however, only approximately 40% of them used condoms consistently during anal sex with male partners. Unprotected anal sex was identified as a risk factor associated with HIV infection, as was syphilis infection. Local residency status and MSM who received intervention and detection services were the factors that decreased HIV infection risk. Sequence analysis identified the HIV-1 CRF55_01B subtype from MSM for the first time in Yinchuan. Conclusion: The reduction of recent HIV diagnoses is an encouraging sign of successful HIV control measures in MSM in Ningxia. The finding that a high proportion of MSM had knowledge of HIV prevention but still conducted unprotected sex highlights the need for further control measures to change unsafe sexual practices among MSM.
Keywords: prevalence